Association of Primary Health Care quality and use of Telehealth: a cross-sectional study with physicians from the More Doctors Program (Brazilian Journal of Health Research, 2022)
Introduction: Brazil faces the challenge of increasing access to quality Primary Health Care. The Mais Médicos Program aims to increase access to primary care and Telehealth Program aims to increase the quality of care. The association between the presence of Telehealth technologies in the doctor’s work and the quality of primary care has not been verified yet in Brazil. Objectives: To analyze the association between global Primary Health Care quality scores and the use of telehealth tools by physicians of the Mais Médicos Program in the state of Espirito Santo, Brazil. Methods: Cross-sectional study in which an online structured questionnaire was applied to physicians in August 2017. The questionnaire contained socio-demographic variables, professional training, length of participation in Mais Médicos, use of the Telehealth Program, and quality of primary care assessed by PCATool. The statistical analysis included a simple description and Kendall rank correlation coefficient. Results: 67 physicians (13.5% of the total) participated. All of them had already used the Telehealth service, predominantly tele-education. Primary health care quality was satisfactory (general score of 7.3 and essential score of 7.0). The specific scores ranged from 4.4 for first-contact access to 8.9 for family counseling. There was no association between the quality of primary care assessed by PCATool and the use of Telehealth. Conclusion: We found no correlation between primary health care quality and the use of telehealth tools.
Keywords: Primary Health Care; Telemedicine; Quality of Health Care; Cross-Sectional Studies